STATIC ANALYSIS OF STRESSES INDIUCED BY MATRIX BAND IN ROOT CANAL TREATED SECOND PREMOLARS MOD CAVITIES BY FINITE ELEMENTH TECHNIQUE - K KHOSRAVI; M MOUSAVINASAB; P KHADEM (Journal of Research in Medical Sciences, 2000)
Introduction. The purpose of this study is measurement the stresses due to matrix bond and their effect on fracture or crock formation in teeth and finally modifying in treatment methods of tooth.
Methods. We use a second premolar that was as similar as measurements of wheelers studies. Au mod cavity prepared with buccolingual width 3mm while the roof of pulp chamber has been removed and gingival floor was 1mm higher than CEJ. CTS was prepared in three dimention: crolan, sigital and axial and then tooth model was made based on Nisall program. The forces due to matrix band measured by strain guage and then, this force based on finite element method applied on the prepared model.
Results: Inall cases, stresses observed in tensile and shear from tensile stresses was mainly in cervical one third of buccal cups and shear stress was surronded cervical area of the tooth like as circle. The greatest amount of forces were localized in gingival floor in mesial area and in the enamel with increasing the depth and sidth of cavity. The amount of this stresses increased especially in increasing of depth. With increasing the width and depth cuspal displacment was observed especially in colossal on third which localized in buccal cusp.
Discussion. Matrix band stresses mainly are destructive and cause fractures or at least crack formation in tooth. So its preffered to use thinner band in shorter time as much as possible. using of anatomic bands were prefeved.